Influência do cultivar, do tipo de folha e do tempo de cultivo na medida indireta da clorofila (spad) em mudas de goiabeira - Rozane, Danilo Eduardo (2009)
Foliar nitrogen analysis, also used in routine laboratories, is destructive and not always fast enough for decision making. The objective of this research was to study SPAD measurements, in guava seedlings (Psidium guajava L.) cultivated in a complete nutritive solution, observing the differences between cultivation, times of sampling, and types of evaluated leaves. The experimental design was a completely randomized scheme, with four repetitions, in split lots. The lots consisted of two guava cultivars (Paluma and Século XXI), as sub-lots, the types of leaves (+1, +2 ,and +3), and five sampling times throughout the experimental period (60, 75, 90, 105, and 120 days). It was concluded that the SPAD measurements in guava seedlings are influenced by cultivation, type of leaf, and time of sampling. The third pair of leaves was shown to be more adequate for evaluating the nutritional status of nitrogen in the guava seedlings from the SPAD reading. The guava cultivars presented differences in SPAD readings only at 60 and 90 days, regardless of the type of leaf.